PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER DENGAN QUICK ON THE DRAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR TIK SISWA SMAN 1 BANJARANGKAN PADA SEMESTER GANJIL TAHUN PELAJARAN 2013/2014 - Dewa Ngakan Putu Eka Juniarta; Ni Desak Made Sri Adnyawati; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
This study aims to improve the activity and student learning outcomes in subjects of Information Technology and communication with implementing learning model Numbered Head Together with Quick on the Draw, and evaluate the response of class XI IPS 1 SMAN 1 Banjarangkan. The application of learning models Numbered Head Together with Quick on the Draw. The subjects were students of class XI IPS 1 SMAN 1 Banjarangkan, first semester academic of year 2013/2014, which involved the students as much as 20 students. The design of this study was action based research (ABR), which consists of two cycles. The data collected in this study is the activity and learning outcomes as well as students' response to the application of learning models Numbered Head Together with Quick on the Draw or ICT subjects. Result of the activity students was collected by used observation sheet in every meeting, student learning outcomes data collected through cognitive tests, while the student response data were collected with a questionnaire sheet enclosed. Toke of data on cognitive tests colected in end of each cycle. The results showed that First There was an increased in the activity of student learning, it saw from increased in the average activity of the students. Second There was an increased in student learning outcomes. It saw from the classical completeness students third The average students' response to the implementation of the learning model Numbered Head Together with Quick on the these results indicate that the response of students classified as positive.